Factors Affecting Social Accountability and Community Based Medical Education in Medical Universities: Iran's Educational Development Authorities View Point - Aeen Mohammadi; Fatemeh Manafi; Farangis Shoghi Shafagh Aria; Rita Mojtahedzadeh (Tehran University of Medical Sciences, 2023)
Background and Aim: Social accountability is defined as identifying social problems and needs, planning for resolving them and evaluating the effect of the plans. Considering the vital role in providing public health, the universities of medical sciences are the most important ones for fulfilling this mission and directing their education, research and service activities toward addressing health concerns of the community. Despite of these attempts, social accountability has not realized completely and satisfying yet. The aim of this study was exploring factors affecting social accountability and community-based medical education in universities of medical sciences from Iran's educational development authorities' view point. Materials and Methods: This was a qualitative study performed by Education Development Center of the Ministry of Health and Medical Education in November 2022. Participants were 68 managers of Education Development Centers and 323 managers of Education Development Offices of schools and hospitals of universities of medical sciences in Iran. Participants were assigned to 8 focus groups. Conventional content analysis was used to extract the categories and subcategories. Results: At the first step 541 codes were extracted which were integrated in to 86 ones after defining similarities. These codes then were categorized into 18 sub-categories and 6 categories, namely "Curriculum" including: curriculum revision, approaches, credits and longitudinal themes and new disciplines, "Community-based education" including: educational fields and creating the foundation, "Students" including: students as teacher, educating students and graduates, "Faculty members" including: faculty members' services, motivation and compensation and administration, "Evaluation" including: student assessment and program evaluation, and "Management" including: management and leadership, organizations, Interdepartmental communication and research. Conclusion: In this study a comprehensive collection of factors affecting SA in universities of medical sciences were identified and categorized. These factors that are compatible with medical education context in Iran can be used by top managers and educational administrators as a framework for short and long-term planning.